العلاقة بين نفي زيادة الصفات الإلهية و الفعل الإلهي : دراسة لآراء أبي هاشم الجبائي و ابن سينا و صدر الدين الشيرازي - الخليفي، عبدالحكيم بن يوسف (جامعة البحرين - كلية الآداب, 2014)
يتناول هذا البحث مسألة العلاقة بين نفي زيادة الصفات الإلهية والفعل الإلهي في الفكر الإسلامي وذلك كما نجدها لدى كل من المعتزلة، والفلاسفة المشائيين الإسلاميين والمدرسة الإشراقية. من المعتزلة سيتناول البحث آراء أبي هاشم الجبائي، ومن المشائية الإسلامية سيعرض البحث لآراء ابن سينا، ومن التيار الإشراقي سيعالج البحث أراء صدر الدين الشيرازي. وعلى الرغم من اتفاق هؤلاء المفكرين الثلاثة على القول بنفي زيادة الصفات، إلا أنهم يختلفون في تصورهم لكيفية هذا النفي، وكيفية تفسير الصفات الإلهية، وكان أن انعكس هذا الاختلاف على تصورهم لطبيعة الفعل الإلهي. وما يهدف أليه هذا البحث هو بيان أن هناك علاقة بين كيفية نفي الصفات وتفسيرها وبين تصور كل مفكر للفعل الإلهي هل هو بالأولوية أم بالوجوب فبينما يرى أبو هاشم أن الفعل الإلهي هو بالأولوية، يرى الآخران أنه بالوجوب واللزوم. This paper investigates the relation between the negation of Divine attributes and the nature of Divine action as it is found among the Mutazilah, the Islamic Peripatetic philosophers, and the illuminationist's philosophers. The paper will deal with three thinkers as representatives of these three schools of thought: Abu Hashim al-Jubba'i. Ibn Sina, and Sadr al- Din al- Shirazi respectively. The position of each thinker on the question of the negation of Divine attributes is to be examined first, followed by his perception of the nature of the Divine action. This examination will show us that despite the fact that the negation of Divine attributes is a common stand among these thinkers, the concept of this negation, and the interpretation of Divine attribute as we find it in Abu Hashim al- Jubba'i differ from that of Ibn Sina and Sadr al -Din al- Shirazi. and that their differences on these two questions is reflected on their understanding of the Divine action. While the former believes that although God. in principle, is free not to choose to create the world. His creation of the world is better than not to create it, the two latter think that God creates the world out of necessity.
Keywords: الفكر الإسلامي -- الصفات الإلهية -- الفلاسفة المسلمون -- ابن سينا، الحسين بن عبدالله، ت. 428 هـ -- الصدر الشيرازي، صدر الدين محمد بن بن إبراهيم بن يحيى، ت. 1059 هـ -- الجبائي، عبدالسلام بن محمد بن عبدالوهاب، ت. 321 هـ